How to create a faculty development program that transforms medical education according to actual institutional needs: evidence-based approach and experience at the University of Rijeka, Faculty of Medicine, Croatia - Pereza, Nina; Hauser, Goran; Dević Pavlić, Sanja; Marić, Ivana; Sotošek, Vlatka; Grgasović, Tina; Mršić-Pelčić, Jasenka (Frontiers in Medicine, 2025)
AimAlthough previous studies demonstrated short, medium and long-term effectiveness of faculty development programs (FDP) for medical teachers, there is a lack of studies describing the methodology for creating a sustainable comprehensive FDP in medical education. We present the methodology for creating the “Modern and Practical Medical Education (MPME),” a comprehensive four-month educational FDP tailored to actual institutional needs, and the initial results of its implementation and transformation of medical education at the University of Rijeka, Faculty of Medicine, Croatia (EU).Materials and methodsWe conducted a multi-phase mixed-method cross-sectional study from July 2021 to June 2024 consisting of three steps: (1) construction of MPME FDP basic structure according to local/national priorities/specificities, literature and expertise, (2) a 360-degree current state analysis for adaptation of basic structure to actual institutional needs, and (3) analysis of the FDP education effectiveness. Step 2 included syllabi analyses and group interviews with 65 teachers’ at 8 departments (qualitative), as well as the analysis of medical students’ perspective using the “Medical students’ questionnaire” on 236 participants (quantitative), and 23 interviews with 8 participants using the “Medical students’ focus group” (qualitative). Step 3 included the quantitative analysis of 40 medical teachers’ self-assessments for 30 teachers’ competencies before and after MPME education using the “MPME questionnaire,” and qualitative analysis of measurable program outcomes.ResultsThe MPME FDP consists of three major modules with seven courses, and is based on a tripartite flipped classroom model. The results of qualitative and quantitative 360-degree analysis identified common weak spots in teachers’ competencies, which were used for program development. Program effectiveness was demonstrated through a highly significant change in the self-assessment for all 30 teachers’ competencies before and after education (p < 0.001), and numerous measurable educational outcomes.ConclusionThe creation of a comprehensive and sustainable FDP in medical education should be based on a three-step quantitative and qualitative process that includes the 360-degree analysis of actual institutional needs, and the effectiveness of the program education. This methodology has a highly significant positive effect on teachers’ competencies at the individual level, and creation of educational projects that transform medical education at the institutional level.